(untitled) (International Journal of Engineering and Computer Science, 2017)
-It is important to understand the architecture of Non linear systems and the components that are responsible for introducing nonlinear distortion. In order to evaluate the effect of nonlinear distortion on system performance the modeling and simulation is the requirement of present scenario of modern wireless communication systems. We have presented the orthogonalization of the behavioral model is beneficial for the better prediction of nonlinear distortion and extracts the uncorrelated component of the nonlinear output that is responsible for the degradation of system performance. Orthogonalization of power series nonlinear model is performed.